Colibacillosis in a New Zealand white rabbit (Oryctolagus cuniculus) - Melissa Saravia; Cristopher Segovia; Katherinne Valderrama; Javier Santander (Journal of Infection in Developing Countries)
Colibacillosis is a disease caused by Escherichia coli in a variety of animals, including humans. Rabbit colibacillosis is infrequent or with an incipient description in Chile. Here, we describe an E. coli case in a white New Zealand rabbit at an animal facility in Santiago, Chile. Necropsy, histology, bacteriology, and 16S sequencing indicated an E. coli systemic infection. Phylogenetic analysis suggested that this E. coli J305 isolate is closely related to Shigella spp.